FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI KECIL DAN MENENGAH DI WILAYAH KOTA DAN KABUPATEN KEDIRI TAHUN 2010-2016 - Minartiningtyas, Putri (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to analyze the variables that affect the absorption of labor in small and medium industries in the regency and city Kediri. In this study using quantitative research methods. And data collection techniques in this study with data collection in various related Offices and interviews. The analysis used is the classical assumption test and multiple linear regression with the help program of Eviews 9.0. The independent variables in this study are regional minimum wage (x1), number of unit (x2), production value (x3) and investment value (x4), while the dependent variable is the amount of labor absorption (Y). The results of this study are variable wages, number of units, production value and investment value have a significant effect on the absorption of manpower, besides the independent variable that gives the most dominant influence on labor absorption is Investment Value (x4)Key words : Employment, regional minimum wage, Number of units, value of Investment, value of production.